Bright V‐Shaped bis‐Imidazo[1, 2‐a]pyridine Fluorophores with Near‐UV to Deep‐Blue Emission. Issue 23 (26th October 2022) - Jouaiti, Elise; Giuso, Valerio; Cianfarani, Damien; Kyritsakas, Nathalie; Gourlaouen, Christophe; Mauro, Matteo
Abstract: Ten novel small‐molecule fluorophores containing two electron‐accepting imidazo[1, 2‐ a ]pyridine (ImPy) units are presented. Each ImPy core is functionalized at its C6 position with groups featuring either electron accepting (A) or donating (D) properties, thus providing emitters with general structure X−ImPy−Y−ImPy−X (X=either A or D; Y=phenyl or pyridine). The molecules bear either a phenyl (series 4 ) or a pyridine (series 5 ) π bridge that connects the two ImPys via meta (phenyl) or 2, 6‐ (pyridine) positions, yielding an overall V‐shaped architecture. The final compounds are synthetized straightforwardly by condensation between substituted 2‐aminopyridines and α‐halocarbonyl derivatives. All the compounds display intense photoluminescence with quantum yield (PLQY) in the range of 0.17–0.51. Remarkably, substituent effect enables tuning the emission from near‐UV to (deep‐)blue region while keeping Commission Internationale de l'Éclairage (CIE) y coordinate ≤0.07. The emitting excited state is characterized by a few nanoseconds lifetime and high radiative rate constant, and its nature is modulated from pure π‐π* to intramolecular charge transfer (ICT) by the electronic properties of the peripheral X substituent. This is further corroborated by the nature of the frontier orbitals and vertical electronic excitations computed at (time‐dependent) density functional level of theory (TD‐)DFT. Finally, this study enlarges the palette of bright deep‐blue emitters based on the interesting ImPy scaffolds in view of their potential application as photo‐functional materials in optoelectronics. Abstract : A novel class of bright V‐shaped chromophores is presented that feature imidazo[1, 2‐ a ]pyridine units. The emitters possess an overall X−ImPy−π−ImPy−X architecture, where X=either electron‐acceptor or electron‐donor group. Photoluminescence is modulated from the near‐UV to the deep‐blue region by the electronic character of the peripheral groups that also influence the nature of the emitting excited state.